Optimum fine and coarse aggregates proportion to produce concrete strength - Johin, Goko (Universiti Malaysia Sarawak (UNIMAS), 2000)
Nowadays, concrete has becoming more and more important in any construction works. There will be no progress in development without concrete. Almost all mega projects in this country involve the using of large amount of concrete. As demand for concrete increases, thus the price of cement (main component in concrete production) also increases. Because of this, more money need to be spent on concrete. Because of that, something needs to be done in order to cut down the expenditure on this material. In this final year project, quarry chip will be introduced as a new ingredient in making concrete. Quarry chip can be collected for free from a quarry since it is a waste product of rock crushing. Thus, there will be no problems arise due to shortage of this material. The project will be mainly based on experimental works. These experimental works were done in a laboratory where all the equipment and materials were kept. The purpose of this study is to have a look on the influence of quarry chip on concrete strength. Beside that, there will also test conducted on the fresh concrete such as slump test and flow table test. From observation, it is found that concrete mixed with quarry chip is more dry and stiff, compare to normal concrete Vvith the same design. By using different amount of quarry chip for each batch of concrete mixed, the concrete strength produced will vary. As the amount of quarry chip is increased, the concrete strength will also increase. Thus, this proves that quarry chip affects concrete strength in a good manner. The findings are really reliable, as there is no admixtures used in the mixing. If this result is accepted by all, then it is said that a more economical way of producing concrete with high strength has been found.